Estudo sistemático da condutividade iônica de vitrocerâmicas NASICON: influência de tratamentos isotérmicos e novas substituições iônicas - Ortiz Mosquera, Jairo Felipe (2020)
The synthesis of solid electrolytes and the optimization of their ionic conductivity are topics of scientific interest since these components are essential for the current density and the half-life of the sodium batteries. The NASICON (Na super-ionic conductor) materials belong to the most promising candidates to solid electrolytes because their 3D structural framework favors the migration of ions. The glass-ceramic route allows the synthesis of NASICON compounds with the advantages of reducing porosity and controlling the microstructure, which are relevant factors in the optimization of ionic conductivity. Thus, in this doctoral thesis NASICON glass-ceramics of the Na1+xAlxGe2-x(PO4)3 (NAGP), Na1+xGe2(SiO4)x(PO4)3-x (NGSP) and Na3.4AlxSc2-xSi0.4P2.6O12 (NAScSP) series have been synthetized. Isothermal heat-treatments of crystallization were performed on NAGP precursor glasses to analyze their effect on structural and electrical properties of the crystallized samples. It was noted that the extensive dealumination of the NASICON phase with the increase of the treatment time does not affect the electrical properties of the material due to the formation of a conductive Na7(AlP2O7)4PO4 phase and a greater contact area between the grains of the glass-ceramics. In the NGSP NASICON series, it was evaluated the effect of Si4+/P5+ substitution on structural and electrical properties of the glass-ceramics. It was confirmed the increment in the ionic conductivity due to the expansion of the unit cell of the NASICON structure and the increase of Na+ ions. In the NAScSP series, it was proven that the addition of Al2O3 favors the glass-forming ability and affects the ionic transport in the material due to a decrease in the bottleneck of NASICON structure.